LAPAROSCOPIC THREE PORT SLEEVE GASTRECTOMY - Kirkil, C.; Aygen, E.; Korkmaz, M. F.; Aktimur, R. (Springer, 2016)
[Abstract Not Available]
21st World Congress of International-Federation-for-the-Surgery-of-Obesity-and-Metabolic-Disorders (IFSO) -- SEP 28-OCT 01, 2016 -- Rio de Janeiro, BRAZIL
Keywords: Sleeve gastrectomy; Minimally invasive; Port